2020
DOI: 10.1016/j.heliyon.2020.e04084
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia: impact of cell phone use and time to rest among teacher students

Abstract: Nomophobia is one of the modern pathologies that has been born as a consequence of the impact that portable technologies have had on society and the dependence generated among citizens, especially towards smartphones. This phobia manifests itself and is intensified by the loss of immediate access to information, to the network of contacts, as well as by the impossibility of contacting or being contacted by other people. All this ends up interfering with the development of the person's daily life (physical, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
(67 reference statements)
2
14
0
3
Order By: Relevance
“…Notably, the outcomes of the current study demonstrate that the principal anxiety of students is exhibited on the construct "Not being able to communicate" as the construct received the largest scores. This finding supports the study by Moreno-Guerrero et al [ 19 ], and other studies [ 15 , 17 , 69 73 ] carried out on similar population. In their studies, they found that "Not being able to communicate" garnered the highest scores among the four constructs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Notably, the outcomes of the current study demonstrate that the principal anxiety of students is exhibited on the construct "Not being able to communicate" as the construct received the largest scores. This finding supports the study by Moreno-Guerrero et al [ 19 ], and other studies [ 15 , 17 , 69 73 ] carried out on similar population. In their studies, they found that "Not being able to communicate" garnered the highest scores among the four constructs.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of nomophobia among distinct populations, notably adolescents [ 67 ], the youth [ 19 ] and higher education students [ 9 , 50 , 58 ], has been evidenced in several studies. Besides, studies have demonstrated that young adults (university students) routinely experience the highest nomophobia prevalence; and, the prevalence ranges between 77 percent and 99 percent among emerging and developed nations [ 44 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, technology, specifically mobile devices, is fully immersed in our society. One example of this is the smartphone, which is used and used today by practically the entire population, from children to adults, to access mainly information [ 1 ] and to be able to communicate with others [ 2 ]. We are probably looking at a device whose characteristics—its portability, ubiquity and immediate access—allow society to access the Internet from anywhere and at any time [ 3 ], being with it 24 h a day, 7 days a week [ 4 ], thereby provoking new habits and actions on the part of people in their daily lives [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An effective intervention should be developed for nomophobia and other communicational problems of students because of the psychological, emotional, and academic impairments of students with nomophobia symptoms and cellphone overuse (11,(23)(24)(25). If proper treatments are used, it will be possible to avoid such disorders and vulnerability of students to emotional, academic, social, and behavioral problems (26).…”
Section: Introductionmentioning
confidence: 99%